2003
DOI: 10.1046/j.1365-2265.2003.01697.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum reverse triiodothyronine levels at diagnosis of hepatocellular carcinoma in patients with compensated HCV‐related liver cirrhosis

Abstract: Our study has demonstrated that development of hepatocellular carcinoma is accompanied by a significant increase in serum rT3 levels in patients with low-grade HCV-related liver cirrhosis who had no other illness causing the 'euthyroid sick syndrome'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…Disruption of TH signaling causes dysfunction in several organs and is closely associated with several diseases [17, 9]. The liver is one of the major target organs of TH, and TH levels are closely correlated with multi liver-associated diseases within a spectrum ranging from hepatic steatosis to HCC [23, 111, 115]. Thus, the complex mechanism of TH action requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disruption of TH signaling causes dysfunction in several organs and is closely associated with several diseases [17, 9]. The liver is one of the major target organs of TH, and TH levels are closely correlated with multi liver-associated diseases within a spectrum ranging from hepatic steatosis to HCC [23, 111, 115]. Thus, the complex mechanism of TH action requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study revealed that the serum levels of THs are decreased in HBV- and HCV-infected patients [17]. HCC is accompanied by a significant increase in serum rT 3 (inactive form of T 3 ) levels in patients with low-grade HCV-related liver cirrhosis [115]. Thus, it is important to determine the functions of TH signaling in HCC.…”
Section: Roles Of Thyroid Hormones and Thyroid Receptors In Liver mentioning
confidence: 99%
“…Conversion of inactive to active thyroid hormone is the result of 5'-deiodination of T4 and occurs in the liver. 30 Peripheral suppression of thyroid hormone activity also occurs in 'non-thyroidal illness syndrome' (previously call the 'sick euthyroid syndrome'). Acute and chronic stress also affects the hypothalamic-pituitary-adrenal axis, which may in turn have several different effects on thyroid function.…”
Section: Hormonal Dysfunction A) Hypothyroidismmentioning
confidence: 99%
“…5 Liver is one of the major target organs of T 3 , and body TH levels are closely correlated with multiple liver-associated diseases, such as hepatocellular carcinoma (HCC). 6, 7, 8, 9 …”
mentioning
confidence: 99%